Fabrication and characterization of forward osmosis hollow fiber membranes with antifouling NF-like selective layer - Setiawan, Laurentia (2013)
A new type of forward osmosis (FO) hollow fiber membranes with an antifouling nanofiltration (NF)-like selective layer has been developed in this work. The fabrication involves a step of porous poly(amide-imide) (PAI) ultrafiltration (UF) hollow fiber spinning via phase inversion, followed by simple polyelectrolyte post-treatments using positively charged polyethyleneimine (PEI) for cross-linking and negatively charged polystyrene sulfonate sodium salt (PSS) for deposition.